The Preventive Detention of “Dangerous” Sex Offenders in Australia: Perspectives at the Coalface - Keyzer, Patrick; McSherry, Bernadette (International Journal of Criminology and Sociology, 2013)
<!-- [if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> <!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]--><span style="font-size: 10.0pt; mso-bidi-font-size: 12.0pt; font-family: 'Times New Roman','serif'; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Four Australian states, Queensland, New South Wales, Western Australia and Victoria as well as the Northern Territory have enacted laws that enable the continued detention in prison of “dangerous” sex offenders beyond the completion of their sentence. This has proved to be a popular response from a political and social policy perspective, with the New South Wales government recently extending its scheme to include serious violent offenders. While the Queensland scheme has been upheld by the High Court of Australia as constitutional, preventive detention laws raise human rights issues and problems with implementation. This paper outlines the results of 86 interviews carried out with psychiatrists, psychologists, social workers, former corrective services officials, lawyers and police officers who have firsthand experience with the operation of the Australian schemes. The results indicate that those at the “coalface” in relation to post-sentence preventive detention schemes are critical of a number of matters such as the general reliance on preventive detention rather than rehabilitation, the reliance on and use of risk assessment tools as well as media reporting of sex offenders.